Hubungan antara Kematangan Emosional dengan Parenting Stress pada Ibu Bekerja di Kecamatan Lubuk Sikaping Kabupaten Pasaman - Mayasti, Sinta; Magistarina, Elrisfa (Lembaga Yasin AlSys, 2024)
This research aims to determine and analyze the relationship between emotional maturity and parenting stress for working mothers in Lubuk Sikaping district. Emotional maturity can be interpreted as the ability a person has to manage emotions effectively in dealing with various situations. Parenting stress is the pressure or tension felt by a mother when carrying out her role and responsibilities in caring for her child. This research uses quantitative methods with a correlational approach. A total of 170 working mothers in Lubuk Sikaping district who have children aged 0-18 years participated in this researh. Data was collected and a parenting stress scale. The results of the analysis show that there is no significant relationship between emotional maturity and parenting stress (pearson correlation -,112 and significant 0.151 (p>0.05). the result of this study identify that emotional maturity does not influence the level of parenting stress experienced by working mothers in Lubuk Sikaping district.